STRENGTHENING MULTISECTORAL GOVERNANCE FOR STUNTING REDUCTION IN INDONESIA: A COMPREHENSIVE POLICY ANALYSIS AND INTERNATIONAL COMPARATIVE REVIEW - Syed Agung Afandi; Muslim Afandi; Rizki Erdayani (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2026)
Multi-level governance deficits and fiscal asymmetries within the decentralized framework constitute primary barriers to accelerating stunting reduction in Indonesia. This study deconstructs subnational institutional matrices and political economies using historical institutionalism (path dependency) and collaborative governance theories. Findings explicitly reveal that a pervasive curative bias within community health centers and the diversion of Village Funds by local elites causally fracture intervention convergence pathways, resulting in household-level nutrient absorption failure. Analytically, an international comparative review of Rwanda’s Imihigo system and Vietnam’s vertical command chain offers novel regulatory benchmarks to overcome localized bureaucratic fragmentation. Core policy recommendations urge binding accountability reforms through mandatory performance contracts for regional leaders and strict fiscal earmarking on central transfer funds conditioned rigorously upon real ground-level nutritional convergence metrics.